An experimental and modeling study of vacuum residue upgrading in supercritical water. Issue 5 (27th February 2018) - Gudiyella, Soumya; Lai, Lawrence; Borne, Isaiah H.; Tompsett, Geoffrey A.; Timko, Michael T.; Choi, Ki‐Hyouk; Alabsi, Mohnnad H.; Green, William H.
Abstract : Arabian Heavy crude oil was fractionated into distillate and vacuum residue fractions. The vacuum residue fraction was treated with supercritical water (SCW) at 450°C in a batch reactor for 15–90 min. The main products were gas, coke, and upgraded vacuum residue; the upgraded residue consisted of gasoline, diesel, and vacuum gas oil range components. The molecular composition of gas and upgraded vacuum residue was analyzed using gas chromatography (GC, GC × GC). SCW treatment converted higher carbon number aliphatics (≥C21 ) and long‐chain (≥C5 ) alkyl aromatic compounds into C1 C20 aliphatics, C1 C10 alkylaromatics, and multiringed species. The concentrations of gasoline and diesel range compounds were greater in the upgraded product, compared to the feed. A first‐order, five lump reaction network was developed to fit the yields of gas, coke, diesel, and gasoline range components obtained from SCW upgrading of vacuum residue. Distillation of crude oil followed by SCW treatment of the heavy fraction approximately doubled the yield of chemicals, gasoline, and diesel, while forming significantly less coke than conventional upgrading methods. © 2018 American Institute of Chemical Engineers AIChE J, 64: 1732–1743, 2018